Analisis Penerapan Laik Higiene Sanitasi Pada Depot Air Minum (DAM): (Studi pada DAM di Daerah Kerja Puskesmas Sugio Lamongan Tahun 2021) - Ainul Fitroh; Ferry Kriswandana; Ernita Sari (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
DAM managers have to make sure the protection of water ate up via way of means of the network meets first-rate standards. Sanitary hygiene rules on DAM manufacturing water remedy have to consist of premises, equipment, fisherizers and uncooked water. The implementation of dam manufacturing water first-rate supervision serves to save you the onset of fitness risks. This studies objectives to research the Application of Sanitary Hygiene Laik on the Drinking Water Depot (DAM) withinside the Sugio Lamongan Health Center Work Area in 2021. Research is analytical via a pass sectional method to the populace taken on this take a look at of 30 DAM. The pattern from this take a look at amounted to 24 DAM In The Sugio Lamongan Health Center Work Area. The approach of taking samples is easy random sampling. Data evaluation strategies use statistical evaluation software. The outcomes of calculations withinside the take a look at acquired a cost of p = 0.013 (α<0.05) withinside the thing of vicinity, equipment (p = 0.013), toucher (p = 0.031) and uncooked water (p = 0.013) in order that it could be concluded that the thing of the vicinity influences the content material of coliform micro organism consuming water DAM manufacturing withinside the Sugio Lamongan Health Center In 2021. The neighborhood Health Office / Health Center is suggested to behavior counseling sports, schooling on dam sanitation hygiene and dam owners / fishermen are anticipated to enforce DAM sanitation hygiene sports primarily based totally on Permenkes RI Number forty three of 2014.